Accounting Education for MSMEs: Enhancing Financial Literacy in the Menari Tourism Village, Semarang Regency - Sasongko, Noer; Erma Setiawati; Lulu Hardiana; Nurlita Arum S (Universitas Muhammadiyah Surakarta, 2025)
This community service activity aims to enhance the understanding of Micro, Small, and Medium Enterprises (MSMEs) in Desa Wisata Menari, Semarang Regency, regarding the importance of accounting in managing business finances. Many MSME owners still lack adequate knowledge of financial recording, which hinders efficiency and decision-making. Through socialization sessions and interactive discussions, participants were introduced to basic accounting concepts and simple bookkeeping practices applicable to their businesses. The results showed an increased awareness of the importance of accounting and an initial ability to perform basic financial recording.